Cartographic monitoring of quality of higher education - Дудун, Тетяна Володимирівна (Київський національний університет імені Тараса Шевченка, 2017)
Викладено підходи до визначення поняття «якість вищої освіти». Обґрунтовані основні критерії і показники, які покладені в основу її картографічного моніторингу. Дано визначення поняття «картографічного моніторингу якості вищої освіти». Проведення картографічного моніторингу зорієнтоване на основні аспекти якості вищої освіти: якість результату, якість умов, якість процесу. Представлено показники для трьох карти які характеризують вищі навчальні заклади України в дзеркалі науко метричної бази даних Sciverse Scopus, загальний рейтинг університетів світу.

The paper deals with the approaches to determination of the notion “quality of high education”. The fundamental criterions and indeces, which be the base of cartographic monitoring are grounded. Construction of cartographic monitoring direct to main aspects of the quality of high education: quality of the result, quality of conditions, quality of a process. The types of higher education institutions and objective factors for stimulating and developing higher education in Ukraine are identified. The concept of “quality of education” is substantiated, the system of indicators of its estimation and cartographic monitoring is given.Cartographic monitoring focuses on the main aspects of the quality of higher education: the quality of the result, the quality of the conditions, the quality of the processes. The main purpose of indicators for monitoring higher education of Ukraine is determined. The indicator is understood as meaningful statistics that provide information on conditions, stability and change, functioning or achievement of the higher education system. It is proved that the modern educational space is characterized by two types of models of educational indicators: international and national ones. The necessity of creating a system of cartographic monitoring of higher education in Ukraine is proved. Its basis will be the quality, efficiency and cost of training per student. The quality of higher education is the number of academic hours, the filling of educational institutions, the qualifications of the teaching staff. Efficiency: data on admission to different levels of education, the number of students who left education before completing it. The analysis of the cost of training per student from different higher educational institutions allows us to estimate the correspondence of expenses to the tasks set. This group of indicators today is the most difficult in terms of data closure and the complexity of the structure of financing expenditures for higher education Three maps that characterize the high educational institutions of Ukraine in looking of science metric of the database Sciverse Scopus, a general rating of high educational institutions of Ukraine, a geometric rating of the universities of the world.
Картографічний моніторинг якості вищої освіти
Вахрушин В., Горбань О. Якість вищої освіти та сучасні підходи до її вимірювання. // Освіта і управління. – 2012, т.15, № 1. – с. 7 – 11. Вебометричний рейтинг університетів світу // Освіта і управління. – 2012, т.15, № 1. – с. 7 – 11. ДСТУ ISO 9000 : 2007. Системи управління якістю. Основні положення та словник термінів. – К., Держспоживстандарт України, 2008. – 34 с. Закон України від 01.07.2015 року № 1556 –VII «Про вищу освіту». Компас – 2013. Рейтинг ВНЗ України // Освіта і управління. – 2013, т.16, № 1-2. – с. 173 – 188. Наука України в дзеркалі науко метричної бази даних Sciverse Scopus від 26 червня 2013 р. // Освіта і управління, т.16, № 1-2, – с. 166 – 171. Освітні реформи: місія, дійсність, Монографія (за ред. В. Кременя та інш.). – К.: ТОВ «Видавниче підприємство «Едельвейс», 2013. – 460 с. Основні показники діяльності вищих навчальних закладів України на початок 2014/2015 навчального року // Стат. Бюлетень. – К., Держ. служба статистики. – 2016. – 219 с. Паращенко Л. Наукове обґрунтування критеріїв і показників для національної системи моніторингу якості освіти // Освіта і управління. – 2009, т.12, №3-4. – С. 110-116. Січкаренко Г. Початок структурних перетворень в системі вищої освіти незалежної України. // Освіта і управління. – 2012, т.15, №2-3. – с. 73 -79.
Keywords: вища освіта; картографування вищої освіти; якість вищої освіти; науково метричні бази; higher education; mapping of higher education; quality of higher education; scientific metric bases